2023
DOI: 10.1186/s13034-023-00590-2
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in symptom structure of adolescent problematic internet use: A network analysis

Abstract: Background Gender differences in problematic Internet use (PIU) have long been discussed. However, whether and how female and male adolescents differ in central symptoms and symptom associations are not fully understood. Methods As a national survey in the Chinese mainland, 4884 adolescents (51.6% females; Mage = 13.83 ± 2.41) participated in the present study. This study applies network analysis to identify central symptoms of PIU networks in fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Prior studies have highlighted variations in internet usage patterns between males and females, with some research indicating that females tend to be more active on social media, whereas males may be more immersed in diverse online activities (Khan et al, 2017). Previous investigations have further indicated that females exhibit higher usage of social media platforms, while males are more prominently involved in online gaming (Liu et al, 2023;Pantu, 2018;Shan et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies have highlighted variations in internet usage patterns between males and females, with some research indicating that females tend to be more active on social media, whereas males may be more immersed in diverse online activities (Khan et al, 2017). Previous investigations have further indicated that females exhibit higher usage of social media platforms, while males are more prominently involved in online gaming (Liu et al, 2023;Pantu, 2018;Shan et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies (Dufour et al, 2016;Gul et al, 2022;Khan et al, 2017;Liu et al, 2023) have consistently found differences in how males and females use the internet. For example, a study suggest that females may be more active on social media platforms, using them for communication, sharing, and connecting with others.…”
Section: Introductionmentioning
confidence: 93%
“…8,30 The role of this compensatory drive is consistent with what has been found in recent studies: both boys and girls reported that the idea of "not wanting to turn off the internet" after internet use was the most influential factor in PIU. 31 One researcher investigated PIU in Chinese subjects in early, middle, and late adolescence and found that "reluctance to stop using the internet" and "lack of control" were stronger in middle and late adolescence. 32 According to the above, boys and girls have different concerns about the functional experience of the internet, which may explain their different levels of PIU.…”
Section: Literature Review Piu In Early Adolescentsmentioning
confidence: 99%